Tinjauan Rancangan Undang-Undang Keamanan Nasional Indonesia Dalam Perspektif Menghadapi Ancaman Masa Depan (pp. 155-180) - Wempy Pasaribu; M. Mossadeq Bahri; Margaretha Hanita; Hanief Ghafur (JURNAL KEAMANAN NASIONAL, 2023)
A large country like Indonesia should have a law on national security, as a basis for law enforcement and national security stability. Conflicts regarding the authority to take action against threats and enforce the law by the military and/or civilians should have been eliminated by formulating a comprehensive and firm terminology for National Security as a whole. The separation of laws and MPR Decrees regarding the TNI and POLRI clearly describes the duties and powers of each, including the handling and types of threats faced. The problem of "fear" of the takeover of authority by the military if the escalation of threats threatens state sovereignty, should be eliminated by clearly and firmly formulating the clauses of involvement and enforcement powers in the law, to eliminate these concerns. Every potential threat, both from outside and from within the country, should be seen as a serious threat and handled together for the sake of the integrity and stability of the country's security. For this reason, it is time to have the courage to stipulate rules of engagement in every escalation of threats, and the authorities of the agencies involved, as well as government officials who have the right to determine the escalation and involvement of agencies.